Systemic antibiotic selection in skin and soft tissue infections - Purnawan, Shafira Anindya; Budianti, Windy Keumala; Widaty, Sandra (Journal of General - Procedural Dermatology and Venereology Indonesia, 2024)
Background: Antibiotics are used in daily practice. To properly select antibiotics, it is important to pay attention to the definitive diagnosis, class of antibiotic, dose, interval, route of administration, and exact duration of use. Discussion: The World Health Organization (WHO) categorizes antibiotics into three groups: Access, Watch, and Reserve—known as the AWaRe classification—to help guide appropriate usage and combat antibiotic resistance. The Gyssens flowchart serves as a valuable tool for clinicians to qualitatively evaluate antibiotic utilization. In skin and soft tissue infections (SSTIs), treatment strategies are tailored according to the characteristics of the infection, including purulence, necrosis, and overall severity. For mild-to-moderate non-purulent SSTIs, beta-lactam antibiotics, such as penicillin and cephalosporin, alongside lincosamides like clindamycin, are recommended as first-line therapies. In cases of moderate-to-severe non-purulent SSTIs, empirical therapy must account for methicillin-resistant Staphylococcus aureus (MRSA). Meanwhile, purulent SSTIs require an initial incision and drainage, with subsequent treatment options including topical antibiotics for mild cases and systemic antibiotics for more complicated or severe infections. Extensive purulent SSTI in adults is empirically considered MRSA. Conclusion: Control of antimicrobial resistance can be achieved by using antibiotics according to the AWaRe classification and evaluating the use of antibiotics qualitatively using the Gyssens flowchart.